Implementation of enterprise risk management (ERM) in the indonesian manufacturing industry: analysis of factors affecting implementation and disclosure - Judijanto, Loso (Institute of Computer Science (IOCS), 2024)
This study aims to review the aspects that influence the implementation of Enterprise Risk Management (ERM) in the manufacturing industry in Indonesia. In particular, it is expected to know the effects of aspects of independent commissioners, auditor reputation, Risk Management Committee (RMC), ownership control and company scale on ERM implementation and reporting. The sample in the study consisted of publicly listed manufacturing companies on the IDX for the period 2020-2021. The sample was determined based on purposive sampling technique and obtained 90 companies that fit the criteria with a total of 180 annual reports. Multiple linear regression models were used as the basis of analysis. The study findings prove that jointly independent commissioners, auditor reputation, RMC, ownership control, and company scale have a positive influence on ERM implementation and transparency. Partially, auditor reputation, RMC, ownership control, and company scale have a positive influence on the implementation and transparency of ERM reporting, while independent commissioners have no effect. The implication of these results is the importance of paying attention to factors that influence the implementation of ERM to increase the transparency and accountability of companies in managing risk. This is because manufacturing companies in Indonesia face many challenges and risks so it is hoped that ERM implementation can help manage these risks better. However, in this case the implementation of ERM in manufacturing companies in Indonesia also experiences various obstacles and challenges that must be overcome so that ERM implementation can be truly effective and provide the expected benefits in managing risks comprehensively.